Status of internal quality control for thyroid hormones immunoassays from 2011 to 2016 in China. Issue 1 (15th February 2017) - Zhang, Shishi; Wang, Wei; Zhao, Haijian; He, Falin; Zhong, Kun; Yuan, Shuai; Wang, Zhiguo
Abstract : Background: Internal quality control (IQC) plays a key role in the evaluation of precision performance in clinical laboratories. This report aims to present precision status of thyroid hormones immunoassays from 2011 to 2016 in China. Methods: Through Clinet‐EQA reporting system, IQC information of Triiodothyronine and Thyroxine in the form of free and total (FT3, TT3, FT4, TT4), as well as Thyroid Stimulating Hormone (TSH) were collected from participant laboratories submitting IQC data in February, 2011‐2016. For each analyte, current CVs were compared among different years and measurement systems. Percentages of laboratories meeting five allowable imprecision specifications (pass rates) were also calculated. Analysis of IQC practice was conducted to constitute a complete report. Results: Current CVs were decreasing significantly but pass rates increasing only for FT3 during 6 years. FT3, TT3, FT4, and TT4 had the highest pass rates comparing with 1/3TEa imprecision specification but TSH had this comparing with minimum imprecision specification derived from biological variation. Constituent ratios of four mainstream measurement systems changed insignificantly. In 2016, precision performance of Abbott and Roche systems were better than Beckman and Siemens systems for all analytes except FT3 had Siemens also better than Beckman. Analysis of IQC practice demonstrated wide variation and great progress in aspects of IQC rules and control frequency. Conclusion: With change of IQC practice, only FT3 had precision performance improved in 6 years. However, precision status of five analytes in China was still unsatisfying. Ongoing investigation and improvement of IQC have yet to be achieved.